2019
DOI: 10.1177/1178633719852626
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Procalcitonin Testing and Antibiotic Utilization for Acute Exacerbations of Chronic Obstructive Pulmonary Disease

Abstract: Background: The majority of acute exacerbations of chronic obstructive pulmonary disease (AECOPD) are triggered by nonbacterial causes, yet most patients receive antibiotics. Treatment guided by procalcitonin (PCT), a sensitive biomarker of bacterial infection, safely decreases antibiotic use in many controlled trials. We evaluated PCT implementation for inpatients with AECOPD at a large academic hospital. Methods: All patients admitted for AECOPD during the first 6 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…According to the results of a retrospective cohort study conducted by Ulrich et al in 2019, in which records of 238 COPD exacerbation cases were evaluated, the duration of antibiotic administration was not shortened in patients directed by PCT within a 6-month period, and no difference was noted in regard to mortality (71). Meanwhile, it was reported that the rate of 30-day readmissions was reduced in the group, in which PCT was measured compared to the group in which it was not worked up (21% vs. 36%).…”
Section: Pct In Copdmentioning
confidence: 99%
“…According to the results of a retrospective cohort study conducted by Ulrich et al in 2019, in which records of 238 COPD exacerbation cases were evaluated, the duration of antibiotic administration was not shortened in patients directed by PCT within a 6-month period, and no difference was noted in regard to mortality (71). Meanwhile, it was reported that the rate of 30-day readmissions was reduced in the group, in which PCT was measured compared to the group in which it was not worked up (21% vs. 36%).…”
Section: Pct In Copdmentioning
confidence: 99%
“…Levels of CRP in combination with PCT is a reliable index for the detection of bacterial infection in these patients. According to the results of a retrospective cohort study conducted by Ulrich et al in 2019, in which records of 238 COPD exacerbation cases were evaluated, the duration of antibiotic administration was not shortened in patients directed by PCT within a 6-month period, and no difference was noted in regard to mortality [72]. Meanwhile, it was reported that the rate of 30-day readmissions was reduced in the group in which PCT was measured compared to the group in which it was not worked up (21 versus 36%).…”
Section: Copd and Pctmentioning
confidence: 99%
“…For lower respiratory illnesses, these newer tests include rapid viral panels using PCR and the biomarker procalcitonin, the latter of which may be elevated in bacterial infections. The evidence is mixed for the benefit of procalcitonin to guide antimicrobial prescribing in acute exacerbations of COPD 12–15. C-reactive protein (CRP) is a biomarker that may be elevated in a variety of medical illnesses including infection.…”
Section: C-reactive Protein Testing To Guide Antibiotic Prescribing Fmentioning
confidence: 99%